Living with buildings. Wellcome Collection, london, 4 October 2018 – 3 March 2019. Issue 1 (2nd January 2019) - Chrysikou, Evangelia
Abstract: A review of the recent exhibition 'Living with buildings: health and architecture', curated by Emily Sargent, at the Wellcome Collection.